Genetics of Sarcoidosis - Fischer, Annegret; Grunewald, Johan; Spagnolo, Paolo; Nebel, Almut; Schreiber, Stefan; Müller-Quernheim, Joachim (Seminars in Respiratory and Critical Care Medicine, 2014)
Sarcoidosis is a multifactorial and polygenic disorder. Recently, several novel predisposing genes have been identified by genome-wide association studies, and fast progress in molecular technologies such as systematic and large-scale resequencing will aid the discovery of further risk loci and variants. In this article, the current knowledge of its genetics will be presented, including known and candidate risk variants and loci, with a focus on loci in the human leukocyte antigen region. Some of these factors are shared with other, clinically distinct diseases. This may lead to the development of new hypotheses on pathomechanisms, which associate sarcoidosis with other granulomatous disorders but also with diseases with significantly different phenotypes. In the near future system, biology approaches will help unravel the differing and common features of these disorders and allow the development of new therapeutic strategies and tools to predict the course and response to treatment of individual patients.
Keywords: sarcoidosis; genetics; genome-wide association study; HLA